Rancang Bangun Sistem Otomatisasi Rekap Nilai Melalui Pengenalan Karakter Dalam Gambar Berbasis Telepon Genggam - Liliana, Liliana; Pramono, Richard (Jurnal Informatika dan Sistem Informasi, 2015)
The assessment within the teaching process may take many form, such as written test, exam, assignment, etc. Grading are done manually on the exam or test sheet paper. For the assignment of 3D Model Subject, the grades are written on a form glued under the assignment result. This generates problem for teacher when storing the grades in the computer. The adjunct lecturers don’t have any place to store the hardcopy for 2D or 3D assignment. This research designed and developed a system that helps storing the grades, where data (grades) captured automatically based on predetermined percentage for each exam, test, assignment, etc. This can minimize human error factors in storing process. Surveys (interview, questionnaire and direct observation) are done to several teachers that have this problems, followed by generates system requirements, design and implementation of the software. Our system has been tested and shows promising result. The software run on Android based mobile phone and take a photo of preprinted form that attached on the assignment, read the data, and store it. The grades will stored based on their percentage in the database. With this system, grading form/sheet can be stored easily, fast, efficient and effectively; and can shows detailed information for each grades. This system provides minimal error rates, faster grades storing process and increased user –teachers and students- satisfaction.